FENOMENA POSTING MEME DI INSTAGRAM (Studi Pada PNS Bappeda Provinsi Bengkulu) - Indria Indria (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
Social media nowadays is able to be a new media phenomenon which close to the Indonesian society, especially for the adolescents and adults. With the social media power as a cyber characteristic frequently produce the phenomena which have been booming for the social media users themselves. In this research, researchers are interested to review the meme phenomena in Instagram as social media. The type of this research is qualitative research. The informants of this research is public employees (PNS) Bappeda Bengkulu Province as Instagram users which regularly active to post memes using meme pictures on their Instagram accounts. Females are considered to be more expressive in front of people. The results of this research showed that there were three motives behind the memes posting activities by Instagram users, which are for entertaining, love, and soul expression. Moreover, in order to interpret the activities of memes posting which have done by Instagram users, researcher figured two main points which are Instagram users feel observed by followers and give the informations for the intagram followers. Therefore, it can be concluded that the meme phenomena is one of the phenomena which the social media users delivering the messages in the new forms by combining the verbal languages with nonverbal communication (expression). Keywords: Meme, Social Media, Instagram